About the possibility of the extension of the additive arithmetic - Maliaukienė, Livija (Lietuvos matematikos rinkinys, 2002)
In this paper the sequential variant of the additive arithmetic with equality and the non-logical symbols o, t, P, + , = is investigated and the proovable properties of the additional function nit is ascertained.